Dividend payouts of travel and leisure companies in Western Europe: An analysis of the determinants - Bahreini, Mahboubeh; Adaoglu, Cahit (Sage Publications Ltd, 2018)
This study examines the dividend payout determinants of travel and leisure companies in five Western European countries that are ranked among the world's top 10 tourist destinations, namely, France, Spain, Italy, Germany, and the United Kingdom. The study analyzes the sector and carries out a comparative analysis of the subsectors. Panel data random-effects Tobit estimation methodology is used during a 10-year period (2005-2015). In addition to the traditional dividend determinants, sector and country-specific determinants such as leverage, asset intangibility, capital intensity (CI), and effective dividend tax rate are used. The estimation results demonstrate that company size, profitability, investment opportunities, and asset intangibility are positive drivers of dividend payout, whereas the leverage ratio and CI deter dividend payout. Additionally, the study provides international empirical evidence for the positive relationship between investment opportunities and dividend payout. This positive relationship, which is regarded as a puzzle, is unique for companies operating in the travel and leisure sector. The identification of unique dividend determinants and the recognition of differences among the subsectors help investors and managers to shape their investment and financial management decisions.
Keywords: asset intangibility; capital intensity; dividend determinants; hospitality; investment opportunities; tax; travel and leisure